Gastroretentive Dosage Forms: An Approach to Oral Controlled Drug Delivery Systems - Rohilla, Ankur (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACTGastric retentive dosage forms have been developed to provide controlled release therapy for drugs with reduced absorption in the lower gastrointestinal (GI) tract or for local treatment of diseases of the upper GI tract. Gastric retentive dosage forms depends on natural GI physiology such as floating or large tablets that depend on delayed emptying from the fed stomach or the dosage forms that are designed to fight the physiology and avoid emptying in the fasted state through dosage forms of even larger sizes with or without flotation or bioadhesion. Floating systems have been considered as one of the important categories of drug delivery systems with gastric retentive behavior. Floating matrix tablets have been developed to prolong gastric residence time leading to an increase in drug bioavailability. The review article explains the various floating drug delivery systems that are formulated in order to enhance the drug bioavailability. Moreover, the identification of key factors influencing the variability of gastric retention has been discussed.